Functional Qualities of Raw and Processed Melon (Cucumeropsis edulis) Seeds (Biological Sciences - PJSIR, 2006)
Meal samples prepared from raw, boiled, toasted, and germinated melon (Cucumeropsis edulis) seeds and were analyzed for their functional properties. On a dry matter basis, the boiled sample contained 210% water absorption capacity, 66% oil absorption capacity, 65% foaming capacity and 12% least gelation capacity. These values were generally higher than other processing methods and a significant difference (P < 0. 05) existed among the samples. There were also significant differences for protein solubility in the processed samples. The minimum pH of the protein solubility varied as raw (5.5); boiled (5.0); toasted (6.5) and germinated (5.0). Emulsion stability was low in all the samples and boiled sample was the most stable for 24h. Only boiled sample produced foam which collapsed within 25 min.